Friendship, Culture, and Mental Health in Adolescence: A Review of Current Evidence - Mudzakkir; Rizqi, Putri Umrotur (Indonesian Scientific Publication, 2024)
Adolescence is a critical developmental stage where friendship and social support networks significantly influence mental health and behavioral outcomes. This narrative review aims to examine the psychological and sociocultural determinants that shape adolescent peer relationships and their implications for emotional well-being. The review systematically identified relevant literature from databases such as Scopus, PubMed, and Google Scholar, using keywords related to social relationships, friendship, social support, adolescent mental health, and behavioral risks. Studies published between 2014 and 2023 were included based on predefined inclusion and exclusion criteria, focusing on empirical findings from qualitative, quantitative, and longitudinal studies. The findings demonstrate that psychological factors such as self-confidence and resilience are strongly associated with the development and sustainability of adolescent friendships. Resilient adolescents exhibit better conflict management and emotional regulation, resulting in stronger support networks. Simultaneously, sociocultural factors, including societal norms and cultural expectations, influence the structure of these networks, with collectivist cultures emphasizing familial and group-based ties, and individualist cultures favoring autonomy and self-selected relationships. Social support networks are shown to mitigate risks of depression and anxiety, especially when emotional quality and inclusivity are present. However, stigma surrounding mental health remains a significant systemic barrier. Peer-led community programs have demonstrated efficacy in strengthening social bonds and reducing isolation. The review concludes by advocating for culturally sensitive policies and educational programs that address stigma, enhance social integration, and promote mental resilience among youth.